2005
DOI: 10.1016/j.jtcvs.2004.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human antithrombin III restores heparin responsiveness and decreases activation of coagulation in heparin-resistant patients during cardiopulmonary bypass

Abstract: Treatment with recombinant human antithrombin III in a dose of 75 U/kg is effective in restoring heparin responsiveness and promoting therapeutic anticoagulation for cardiopulmonary bypass in the majority of heparin-resistant patients. Two units of fresh frozen plasma were insufficient to restore heparin responsiveness. There was no apparent increase in bleeding associated with recombinant human antithrombin III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 20 publications
1
73
0
Order By: Relevance
“…Potential risk factors for HR include patients older than 65 years old, a platelet count >300,000 cells/ mm 3 , recent heparin exposure, and AT deficiency. [13,14] In our study, 32 of the 54 patients who developed HR were 65 years old or older, and 52 of these 54 had a platelet count of 300,000 or over.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential risk factors for HR include patients older than 65 years old, a platelet count >300,000 cells/ mm 3 , recent heparin exposure, and AT deficiency. [13,14] In our study, 32 of the 54 patients who developed HR were 65 years old or older, and 52 of these 54 had a platelet count of 300,000 or over.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is known as heparin resistance (HR). For patients undergoing heart surgery, many studies have reported the incidence of HR to be between 4 and 22%, [1][2][3][4][5][6][7] with the most frequent causes being AT deficiency, increases in the clearance of heparin the protein that joins with heparin, and high levels of factor 8, fibrinogen, and platelet factor (PF) 4. [8] In addition, HR has also been reported as a result of using medications such as aprotinin and nitroglycerin.…”
mentioning
confidence: 99%
“…[400][401][402][403][404] Studies supporting AT III supplementation for the treatment of heparin resistance include 4 randomized, controlled trials showing prolongation of ACT or a reduction in hemostatic activation. [405][406][407][408][409][410][411][412][413][414][415] AT III concentrate is a stable, lyophilized product derived from pooled normal human plasma, purified, and heat treated at 60°C for 10 hours to eliminate the possibility of viral transmission. 416,417 No cases of viral transmission have been attributed to AT III supplementation.…”
Section: Heparin Resistancementioning
confidence: 99%
“…Historically, CPB has been initiated with higher ACTs to give a margin of safety 28 and in many studies, a large number of patients diagnosed as heparin resistant had target ACTs >400 seconds. [5][6][7][8]13,14 Definitions of heparin resistance based on a dose of heparin to achieve a specific target ACT such as requiring >500 IU/kg to achieve a target ACT of 480 seconds assume linearity of the HDR. 10 Although Despotis et al 29 observed a strong linear relationship between ACT and heparin concentration observed over a range of heparin concentrations, to assume that our results could be extrapolated to higher target ACTs would not be appropriate.…”
Section: Discussionmentioning
confidence: 99%